2016
DOI: 10.1111/dmcn.13026
|View full text |Cite
|
Sign up to set email alerts
|

A special supplement: findings from the Australian Cerebral Palsy Register, birth years 1993 to 2006

Abstract: ABBREVIATIONS ACPRAustralian Cerebral Palsy Register AIM To briefly outline the strengths and limitations of cerebral palsy (CP) registers, and to report on findings of the Australian Cerebral Palsy Register (ACPR) pertaining to a population cohort of children with CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
75
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 22 publications
12
75
0
2
Order By: Relevance
“…In this population the headline frequencies of spasticity and dyskinesia according to PMT were similar to those identified in other population‐based studies . Across the population the degree of dystonia increased as motor function worsened, regardless of PMT.…”
Section: Discussionsupporting
confidence: 83%
“…In this population the headline frequencies of spasticity and dyskinesia according to PMT were similar to those identified in other population‐based studies . Across the population the degree of dystonia increased as motor function worsened, regardless of PMT.…”
Section: Discussionsupporting
confidence: 83%
“…Fifty‐four per cent (54%) of the sample were male, 55 per cent were born preterm, 88 per cent had a spastic CP subtype, 70 per cent were ambulatory with or without assistance (GMFCS level I–III), and 61 per cent had one or more comorbidities (Table ). This approximates (with minor variation) the major features as published of the CP profile for both the CCPR, and for reports from other high resource nations . Almost all (99%) children had received rehabilitation services in the preceding 6 months.…”
Section: Resultssupporting
confidence: 71%
“…The other congenital anomalies identified in the BCPR were also seen in the other registers. [8][9][10][11][12][13][14] Musculoskeletal disorders comprised 10% of congenital anomalies, less than the 23% noted in the Merseyside and Cheshire Cerebral Palsy Register 11 but more than those noted in the Australian, 13 Canadian, 12 and other European CP registers. 9,10,14 Disorders of the eye, digestive system, and cleft lip were found in smaller proportions in the BCPR.…”
Section: Discussionmentioning
confidence: 93%
“…6 Congenital anomalies are more common in children with CP compared to the general paediatric population, both with regard to the central nervous system and other organ systems. [7][8][9][10][11][12][13][14] The Australian Cerebral Palsy Register reported that for the birth years 1993 to 2009, between 15% and 40% of children had a major congenital anomaly. 7 In the Western Australian Birth Defect Registry and Western Australian Cerebral Palsy Register for 1980 to 1994, it was reported that 30.6% of all CP cases had congenital anomalies; 46.2% had cerebral disorders and 53.8% had non-cerebral disorders.…”
mentioning
confidence: 99%